Topical cyclosporine A 0.05% in the treatment of keratoconjunctivitis sicca - Schrell, C.; Cursiefen, Claus; Kruse, Friedrich Eduard; Jacobi, Christina (Klinische Monatsblätter für Augenheilkunde, 2012)
The current understanding of the pathogenesis of dry eye disease has proceeded to recognition of inflammation as the key pathogenetic mechanism. The purpose of this study was to evaluate the effect of cyclosporine 0.05% eye drops on subjective symptoms and objective signs of patients with keratoconjunctivitis sicca.In this clinical trial 62 patients with severe keratoconjunctivitis sicca (DEWS grade 3) were included. Over a time period of 3 months all patients received treatment with preservative-free hyaluronic acid artificial tears at one drop 5 times per day and in addition 31 patients received one drop of cyclosporine 0.05% twice daily. Screening parameters were LIPCOF, tear break-up time (BUT), fluorescein and rose bengal staining, the intraocular pressure (IOP) and the OSDI score.In the cyclosporine A group BUT, Jones test and OSDI score improved significantly after 3 months in contrast to the controls. Moreover the values of BUT and Jones test in the cyclosporine A group were significantly higher after 3 months compared to the healthy controls. Fluorescein and rose bengal staining improved only in the cyclosporine A group after 3 months.Anti-inflammatory therapy with cyclosporine A 0.05% eye drops as off label use significantly improves subjective symptoms and objective signs in patients with severe dry eye disease providing a good safety profile. These findings suggest a widespread use of cyclosporine A 0.05% eye drops in patients with moderate to severe keratoconjunctivitis sicca.
EVALuna2:21106